2022
DOI: 10.3390/foods11172707
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Metabolomics to Decipher the Molecular Mechanisms in the Action of Gut-Modulating Foods

Abstract: Metabolomics deals with uncovering and characterizing metabolites present in a biological system, and is a leading omics discipline as it provides the nearest link to the biological phenotype. Within food and nutrition, metabolomics applied to fecal samples and bio-fluids has become an important tool to obtain insight into how food and food components may exert gut-modulating effects. This review aims to highlight how nuclear magnetic resonance (NMR)-based metabolomics in food and nutrition science may help us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…93−95 It is demonstrated that creatine and creatinine are also associated with mitochondrial muscle respiration, playing a regulation role in adipose tissue metabolism; 96,97 in particular, we can highlight that a potential effect of the probiotics on the protein metabolism is observed even at serum level. 98,99 The decrease of histidine could be directly related to bacterial fermentation; in fact, the gut microbiota converts histidine into an immunoregulatory signal, histamine, able to suppress pro-inflammatory tumor necrosis factor (TNF) production that could generate several local and/or systemic diseases. 78,100 It is also known that the gut microbiota utilizes glutamine as a nitrogen source for optimal survival and growth.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…93−95 It is demonstrated that creatine and creatinine are also associated with mitochondrial muscle respiration, playing a regulation role in adipose tissue metabolism; 96,97 in particular, we can highlight that a potential effect of the probiotics on the protein metabolism is observed even at serum level. 98,99 The decrease of histidine could be directly related to bacterial fermentation; in fact, the gut microbiota converts histidine into an immunoregulatory signal, histamine, able to suppress pro-inflammatory tumor necrosis factor (TNF) production that could generate several local and/or systemic diseases. 78,100 It is also known that the gut microbiota utilizes glutamine as a nitrogen source for optimal survival and growth.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It is demonstrated that creatine and creatinine are also associated with mitochondrial muscle respiration, playing a regulation role in adipose tissue metabolism; 96 , 97 in particular, we can highlight that a potential effect of the probiotics on the protein metabolism is observed even at serum level. 98 , 99 …”
Section: Discussionmentioning
confidence: 99%